Berbamine Analogs Exhibit Differential Protective Effects From Aminoglycoside-Induced Hair Cell Death - Hudson, Alexandria M.; Lockard, Gavin M.; Namjoshi, Ojas A.; Wilson, Joseph W.; Kindt, Katie S.; Blough, Bruce E.; Coffin, Allison B. (Frontiers in Cellular Neuroscience, 2020)
Hearing loss is the third most common chronic health condition in the United States and largely results from damage to sensory hair cells. Major causes of hair cell damage include aging, noise exposure, and medications such as aminoglycoside antibiotics. Due to their potent antibacterial properties and low cost, aminoglycosides are often used for treatment of gram-negative bacterial infections, surpassing expensive antibiotics with fewer harmful side effects. However, their use is coupled with permanent hearing loss in over 20% of patients requiring these life-sustaining antibiotics. There are currently no FDA-approved drugs that prevent hearing loss from aminoglycosides. A previous study by our group identified the plant alkaloid berbamine as a strong protectant of zebrafish lateral line hair cells from aminoglycoside damage. This effect is likely due to a block of the mechanotransduction channel, thereby reducing aminoglycoside entry into hair cells. The present study builds on this previous work, investigating sixteen synthetic berbamine analogs to determine the core structure underlying their protective mechanisms. We demonstrate that nearly all of these berbamine analogs robustly protect lateral line hair cells from ototoxic damage, with ED50 values nearing 20 nM for the most potent analogs. Of the sixteen analogs tested, nine protected hair cells from both neomycin and gentamicin damage. Interestingly, one of the sixteen analogs was protective against just gentamicin and two of the analogs were protective specifically against neomycin. These data are consistent with prior research demonstrating that different aminoglycosides activate somewhat distinct mechanisms of damage. Regardless of mechanism, protection required the entire berbamine scaffold. Phenolic alkylation or acylation with lipophilic groups appeared to improve protection compared to berbamine, implying that these structures may be responsible for mitigating damage. While the majority of analogs confer protection by blocking aminoglycoside uptake, 18% of our analogs also confer protection via an uptake-independent mechanism; these analogs exhibited protection when delivered after aminoglycoside removal. Based on our studies, berbamine analogs represent a promising tool to further understand the pathology of aminoglycoside-induced hearing loss and can serve as lead compounds to develop otoprotective drugs.